Performance of Heat Tolerant Maize Genotypes under Moisture Stress during Rainy Season in Karnataka - Ramesh, Y. M.; Veeresh, H.; Mahadevaswamy, .; Halepyati, A. S.; Koppalkar, B. G.; Kuchanur, P. H.; Chittapur, B. M.; Shwetha, B. N. (Sciencedomain International, 2021)
This research was formulated to study the response of heat tolerant genotypes to prolonged period of water stress prevalent under rainfed situation. The trial was conducted at Agricultural Research Station, Dhadesugur, University of Agricultural Sciences, Raichur, Karnataka, India, during rainy season (kharif) 2019. The present study comprised of three stress tolerant genotypes (RCRMH 2, RCRMH 3 and RCRMH 4) with four moisture stress stages (imposed between 20-40, 40-60, 60-80 and 80-100 DAS) which were sown during June, July and August, and the design employed was Randomized complete block design. The results revealed that superior performance of RCRMH 3 (5321 kg ha-1) over other genotypes whether stressed or not, but all the genotypes were on par with each other in terms of physiological parameters viz., proline accumulation, relative water content, canopy temperature, NDVI, relative chlorophyll content and ASI, and these parameters exhibited good correlation with yield and hence found ideal for stress studies. The present study indicated that these cultivars sustain maize production under moisture stress condition and therefore, are suitable to semiarid region characterized by inclement weather.
Keywords: 2. Zero hunger